2019
DOI: 10.1111/ans.15144
|View full text |Cite
|
Sign up to set email alerts
|

What is the functional result of a delayed coloanal anastomosis in redo rectal surgery?

Abstract: Background: Delayed coloanal anastomosis (DCAA) may be used in patients with complex rectal conditions, such as chronic pelvic sepsis, low recto-vaginal and recto-vesical fistula; however, limited data are available. The aim is to report the morbidity and functional results of DCAA in redo rectal surgery. Methods: All patients undergoing DCAA between January 2014 and August 2017 were retrospectively included. Success was defined as a functional anastomosis without stoma, evaluated using the Low Anterior Resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…Actually, the Italian Society of Colon and Rectal Surgery as well as the German Society of Colorectal disease recommend that the central ligation of IMA should be reserved in cases of suspected malignant disease or when the achieved colon mobilization is not enough to have a tension-free anastomosis [17,18]. In the literature, the influence of a high tie dissection of the IMA on QoL was mostly studied in colorectal surgery for cancer [19][20][21][22]. The hypothesis by which the oncological resection could influence the postoperative QoL is based on anatomical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the Italian Society of Colon and Rectal Surgery as well as the German Society of Colorectal disease recommend that the central ligation of IMA should be reserved in cases of suspected malignant disease or when the achieved colon mobilization is not enough to have a tension-free anastomosis [17,18]. In the literature, the influence of a high tie dissection of the IMA on QoL was mostly studied in colorectal surgery for cancer [19][20][21][22]. The hypothesis by which the oncological resection could influence the postoperative QoL is based on anatomical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The present study reports on a series of 26 DCAA for redo rectal surgery between January 2014 and August 2018. The authors previously reported a high success rate of DCAA with a low morbidity [8], however, this series showed that functional results evaluated with LARS score seem to be better after ICAA than after DCAA, with no difference in quality of life. All Moreover, evolution of functional disorders after rectal resection is poorly described in the literature, although it seems that function improves with time, even up to two years post-operatively.…”
Section: Discussionmentioning
confidence: 61%
“…This technique has been described previously. [8] The second operative procedure (colonic stump resection and handsewn redo-surgery with colo-anal anastomosis) was performed by perineal approach approximately 14 days later.…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations